Knowledge generation and former carers: reflections and ways forward. (1st July 2021) - Larkin, Mary; Milne, Alisoun
Abstract : While their increasing number is achieving some academic and public recognition, former carers occupy a liminal status, are often hidden, and experience a range of negative legacies related to caring. Existing research on former carers is limited in both quantity and quality, and former caring tends to be viewed as an end stage of the overall caring trajectory. A number of theories and concepts employed to enrich the wider carers field have the potential to extend understanding about the needs, situations and lived experiences of former carers and to generate new knowledge about former caring as a process and a transition. These include feminist perspectives, lifecourse analysis, the ethic of care, the emotiospatial hermeneutic, emotional labour, social liminality, hybridity, biographical disruption and social identity. The article aims to open up debate about former carers and act as a platform for taking forward developments in research.